Silicon Germanium Heterojunction Bipolar Transistor for Digital Application - Engelin Shintadewi Julian (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
Bipolar transistor performances can be characterized by figures of merit such as cut-off frequency, maximum frequency of oscillation and Emitter Coupled Logic gate delay. We studied the required figures of merit for digital application and the effects of lateral and vertical scaling to the figures of merit of SiGe Heterojunction Bipolar Transistor. With lateral scaling, the width of emitter finger is scaled down from 0.25 to 0.12 μm while with the vertical scaling, the base width is scaled down to reduce the base delay. We also observed the effects of Ge profile and Ge fraction to the devices performances. Bipole3 5.3.1G is used to help us in the study. We found that high frequency cut-off and maximum frequency of oscillation as well as low Emitter Coupled Logic gate delay are all important for digital applications. Scaling down the emitter finger width enhanced the maximum frequency of oscillation and reduced Emitter Coupled Logic gate delay significantly while scaling down the base width increased the cutoff frequency and current gain.